Coping with a narcissistic partner during lockdown - A qualitative research - Costin, Alina; Rad, Dana (Technium Social Sciences Journal, 2021)
This work is a phenomenological analysis that investigates how the lockdown was perceived by dysfunctional families, namely, narcissistic families. The literature indicates serious disorders in the family life of the narcissist, hostility, tension, conflict, instability (Campbell, Foster, 2002; Kohut, 1972), so, we are interested in describing how narcissistic partners perceive their relationship, and how they describe the period spent during the pandemic restrictions. Two case studies were conducted, which were selected so as to be relevant to the research objectives. We were also interested in the psychological symptoms of the two subjects investigated shortly after the restrictions were lifted. In this regard, the Revised 90 symptom assessment scale (Marian, M.I., 2008) was also applied. The results of this study confirm the negative effects on mental health that a relationship with a narcissistic partner holds during lockdown and encompasses surprising coping strategies that make living with a narcissistic partner possible. Keywords: lockdown, narcissistic family, stress, mental health, coping